BIODEGRADATION OF CHICKEN FEATHER WASTE USING BACILLUS SUBTILIS FOR THE PRODUCTION OF KERATINASE, ITS PURIFICATION AND IMMOBILIZATION WITH POLY (VINYL ALCOHOL)-ASSISTED SILVER NANO-PARTICLES (Journal of Medical & Health Sciences Review, 2025)
The escalating accumulation of chicken feather waste, a byproduct of the poultry industry, has posed significant environmental and public health concerns due to its resistance to conventional degradation methods. Microbial degradation using keratinolytic bacteria has emerged as an eco-friendly and sustainable solution, offering the added advantage of producing valuable enzymes. In this study, Bacillus subtilis was employed for the microbial degradation of chicken feathers via liquid state fermentation to produce extracellular keratinase. Response Surface Methodology (RSM) was utilized to optimize the fermentation parameters, revealing that a pH of 10, inoculum size of 2.5 mL, incubation period of 120 hours, and temperature of 30 °C yielded the maximum keratinase activity of 225.6 U/mL. The enzyme was subsequently purified through ammonium sulfate precipitation, ion exchange chromatography, and gel filtration, resulting in a 5.27-fold purification with 68.19% enzyme recovery and a final specific activity of 250 U/mg. SDS-PAGE analysis indicated a molecular weight of 32 kDa. Furthermore, keratinase was immobilized with silver nanoparticles, leading to a 4.7-fold enhancement in enzymatic activity compared to the free enzyme. FTIR analysis was conducted to compare structural changes in free and immobilized enzymes. The study demonstrates the promising potential of microbial keratinase production from poultry waste for industrial and pharmaceutical applications.